2015
DOI: 10.1111/1753-0407.12301
|View full text |Cite
|
Sign up to set email alerts
|

Risk of overall mortality and cardiovascular events in patients with type 2 diabetes on dual drug therapy including metformin: A large database study from the Cleveland Clinic

Abstract: Background: The aim of the present study was to assess the risk of overall mortality, coronary artery disease (CAD), and congestive heart failure (CHF) in patients with type 2 diabetes mellitus (T2DM) treated with metformin (MF) and an additional antidiabetic agent. Methods: A retrospective cohort study was conducted using an academic health center enterprise-wide electronic health record (EHR) system to identify 13 185 adult patients (>18 years) with T2DM from January 2008 to June 2013 and received a prescrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…Effects on hospital admission for heart failure All five trials 9 evidence from observational studies Of 12 observational studies, four [109][110][111][112] reported heart failure, and eight 13-17 113-115 reported hospital admission for heart failure; nine 13-15 109-111 [113][114][115] were cohort studies and the other three 16 17 112 were nested case-control studies (fig 1). Observational studies reporting heart failure Of the four studies reporting heart failure, two prospective cohort studies 109 (table 4 and table 5).…”
Section: Trials Reporting Hospital Admission For Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Effects on hospital admission for heart failure All five trials 9 evidence from observational studies Of 12 observational studies, four [109][110][111][112] reported heart failure, and eight 13-17 113-115 reported hospital admission for heart failure; nine 13-15 109-111 [113][114][115] were cohort studies and the other three 16 17 112 were nested case-control studies (fig 1). Observational studies reporting heart failure Of the four studies reporting heart failure, two prospective cohort studies 109 (table 4 and table 5).…”
Section: Trials Reporting Hospital Admission For Heart Failurementioning
confidence: 99%
“…All three cohort studies [109][110][111] reported unadjusted rates of heart failure, involving 541 events among 16 408 patients (raw event rate 3.3%). Because of the heterogeneous and indirect nature of the identified evidence-with substantial variations in comparisons and types of patients-we did not pool data across studies.…”
Section: Effects On Heart Failurementioning
confidence: 99%
“…Overall, there were numerically more cardiovascular deaths in the treatment arm versus placebo (7 vs 4 deaths, respectively) with a total of 11 deaths in the vildagliptin arm and 4 deaths in the placebo arm. Heart failure events were reported by Krum et al 10 Four additional relevant publications on different high-risk patient cohorts were also found, one that examined patients with existing CVD drawn from a commercial claims database 14 and a second that studied Cleveland Clinic patients with documented existing CVD, 15 and a third from another commercial database examining only sitagliptin in patients with an acute cardiac event. 16 The fourth publication came from a United Kingdom general practice database.…”
Section: Resultsmentioning
confidence: 92%
“…15 The patients were followed for mortality, coronary artery disease, and congestive heart failure by documentation in the electronic health record. Combination therapy with metformin plus sulfonylurea served as the comparator group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation